Is Lipopolysaccharide-Induced Lipid Metabolism Disorder in Testis of Rats a Consequence of Plasma Lipid Changes? - Zheng X; Li Y; Shang X; Liu R (Dove Medical Press, 2024)
Xiaokang Zheng,1,2,* Yu Li,2,* Xuejun Shang,3 Ranlu Liu1 1Department of Urology, Tianjin Medical University General Hospital, Tianjin Medical University, Tianjin, 300052, People's Republic of China; 2Department of Andrology, Henan Provincial People's Hospital; Zhengzhou University People's Hospital; Henan University People's Hospital, Zhengzhou, Henan, 450003, People's Republic of China; 3Department of Urology, Jinling Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, 210002, People's Republic of China*These authors contributed equally to this workCorrespondence: Ranlu Liu, Department of Urology, Tianjin Medical University General Hospital, Tianjin Medical University, No.154, Anshan Road, Tianjin, 300052, People's Republic of China, Email ranluliu@126.com Yu Li, Department of Andrology, Henan Provincial People's Hospital; Zhengzhou University People's Hospital; Henan University People's Hospital, No.7 Weiwu Road, Zhengzhou, Henan, 450003, People's Republic of China, Email liyu7715@126.comPurpose: The systemic infection and inflammation can result in testes injury, whereas the exact mechanism is unknown. The lipid metabolism has a dual impact on controlling metabolism and inflammation, which is a potential pathway. The objective of this study was to determine if changes in plasma lipids during lipopolysaccharide (LPS)-induced systemic inflammation affect the dysregulation of testes lipid metabolism.Materials and Methods: LPS (5 mg/kg) was used to induce systemic inflammation in rats after a single intraperitoneal injection. After 4 weeks, the rats were sacrificed, and the serum and testes were used for laboratory measurements and histology examination. Plasma and testis were used for lipidomics analysis based the liquid chromatography-mass spectrometry. Spearman rank correlation analysis was used to compare the correlation of differential lipids in phospholipids, glycerolipids, and sphingolipids between testis and plasma.Results: LPS raised the levels of cytokines in serum and testis, decreased the activities of antioxidant enzymes, increased the levels of lipid peroxidation products, and damaged testis tissue. In testis and plasma, 146 and 401 differential lipids, mostly phosphatidylcholine, phosphatidylethanolamine an so on, were found in comparison to the control group. Correlation analysis produced a total of 2528 correlation coefficients, 1150 of which were P< 0.05 and accounted for 45.49%.Conclusion: The changes of lipid composition and content in the testis are related to cytokine overload and oxidative stress. Testis lipid metabolism disorders caused by LPS-induced systemic inflammation are lack of a correlation with plasma lipid changes, and are likely owing to interference with the testis itself.Keywords: systemic inflammation, infertility, lipidomics, oxidative stress, correlation analysis